2016
DOI: 10.1038/tp.2016.42
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of prefrontal cortex myelination by the microbiota

Abstract: The prefrontal cortex (PFC) is a key region implicated in a range of neuropsychiatric disorders such as depression, schizophrenia and autism. In parallel, the role of the gut microbiota in contributing to these disorders is emerging. Germ-free (GF) animals, microbiota-deficient throughout life, have been instrumental in elucidating the role of the microbiota in many aspects of physiology, especially the role of the microbiota in anxiety-related behaviours, impaired social cognition and stress responsivity. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
370
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(413 citation statements)
references
References 63 publications
13
370
2
3
Order By: Relevance
“…An increasing body of evidence suggests a link between microglia and the microbiota-gut-brain axis which has implications for many stress-related and neurodegenerative disorders There is a close link between HPA axis activation and the regulation of the peripheral and central immune responses, leading to monocyte priming and trafficking, subsequent alterations in microglia phenotype and, ultimately resulting in neuroinflammation. Indeed such neuroinflammatory responses are implicated in a number of psychiatric disorders, including anxiety and depression (Hodes et al, 2015;Miller and Raison, 2015). Microglia activation and subsequent release of cytokines plays a causal role in the manifestation of behavioral phenotypes in a variety of rodent stress models (Kreisel et al, 2014).…”
Section: Microbiota As a Regulator Of Neuroimmune Functionmentioning
confidence: 99%
“…An increasing body of evidence suggests a link between microglia and the microbiota-gut-brain axis which has implications for many stress-related and neurodegenerative disorders There is a close link between HPA axis activation and the regulation of the peripheral and central immune responses, leading to monocyte priming and trafficking, subsequent alterations in microglia phenotype and, ultimately resulting in neuroinflammation. Indeed such neuroinflammatory responses are implicated in a number of psychiatric disorders, including anxiety and depression (Hodes et al, 2015;Miller and Raison, 2015). Microglia activation and subsequent release of cytokines plays a causal role in the manifestation of behavioral phenotypes in a variety of rodent stress models (Kreisel et al, 2014).…”
Section: Microbiota As a Regulator Of Neuroimmune Functionmentioning
confidence: 99%
“…It receives sensory inputs from the thalamus and cortical areas as well as extensive inputs from other regions in the limbic system, including the prefrontal cortex and hippocampus, [15] both of which are markedly altered in germ-free (GF) animals. [10,12,16] In fact, the connectivity between these three major regions, not just the function of the individual structures, is fundamental to appropriate emotional responses. [17] Although tracer studies have shown afferents reaching all amygdala nuclei, sensory inputs often reach the amygdala through the LA while inputs from other brain regions target primarily the LA and BLA.…”
Section: The Amygdalamentioning
confidence: 99%
“…[7] Thus far, the use of microbial manipulations to test for brain region-specific effects has largely focused on the hippocampus and the prefrontal cortex. [8][9][10][11][12] However, we are now beginning to understand that the same microbial manipulations may also have implications for the amygdala.…”
Section: Introduction: the Microbiota-gut-brain Axismentioning
confidence: 99%
“…1 , 2 The ‘gut-brain axis‘ had already been studied before this field of research gained new momentum a decade ago with the characterization of the gut microbiome. 3 Although the underlying molecular mechanisms remain elusive, the gut microbiota has been shown to modulate behavior and brain processes, including pain perception, 2 stress responsiveness, 4 prefrontal myelination, 5 and brain biochemistry. 1 Experimental manipulation of the gut microbial community composition was shown to be able to modify the host's neural function.…”
Section: Introductionmentioning
confidence: 99%
“…1 The gut microbiota was found to influence the process of myelination in frontal brain regions, suggesting a role of gut microbiota in higher-order cognitive functions, in addition to emotional processing. 5 …”
Section: Introductionmentioning
confidence: 99%